2008
DOI: 10.1158/1535-7163.mct-07-0560
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitors induce growth arrest, apoptosis, and differentiation in clear cell sarcoma models

Abstract: Clear cell sarcoma is an aggressive malignancy occurring most commonly in the distal extremities of young adults, characterized by t(12;22)(q13;q12) creating the chimeric fusion oncoprotein EWS-ATF1. We assessed growth inhibition and differentiation effects of histone deacetylase inhibitors MS-275 and romidepsin (depsipeptide, FK228) on clear cell sarcoma cells and evaluated drug sensitivity among related translocation-associated sarcomas and other cell models. Three clear cell sarcoma cell lines, seven other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 42 publications
3
31
0
Order By: Relevance
“…146 HDAC inhibitor will reverse the repression by the Polycomb protein, leading to de-repression of EGR1 and followed by apoptosis. Similar preclinical anti-tumour effect has been observed in Ewing sarcoma, [147][148][149] clear cell sarcoma, 150 endometrial stromal sarcoma, 151 mxyoid chondrosarcoma 152 and alveolar rhabdomyosarcoma. 149 Treatment of HDAC inhibitor leads to increase in expression of p21 and G2/S arrest and decrease in mTOR expression and activity, leading to apoptosis and autophagy.…”
Section: Histones and Histone Deactylasesupporting
confidence: 70%
“…146 HDAC inhibitor will reverse the repression by the Polycomb protein, leading to de-repression of EGR1 and followed by apoptosis. Similar preclinical anti-tumour effect has been observed in Ewing sarcoma, [147][148][149] clear cell sarcoma, 150 endometrial stromal sarcoma, 151 mxyoid chondrosarcoma 152 and alveolar rhabdomyosarcoma. 149 Treatment of HDAC inhibitor leads to increase in expression of p21 and G2/S arrest and decrease in mTOR expression and activity, leading to apoptosis and autophagy.…”
Section: Histones and Histone Deactylasesupporting
confidence: 70%
“…35 By analogy, a dependence on HDAC2 activity for cell cycle progression in translocationassociated sarcomas could contribute to their particular sensitivity to HDAC inhibitors. 18 In summary, HDAC2, one of the HDAC isoforms and a therapeutic target for HDAC inhibitors, is present and intensely expressed in a very high proportion of mesenchymal tumors. Expression is highest among sarcomas associated with fusion transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…Total protein lysates from SYO-1 and DTC1 cell lines 18 were prepared using RIPA buffer containing sodium chloride 150 mM/l, 1% NP-40, 0.5% sodium deoxycolate, 0.1% sodium dodecyl sulfate, 50 mM/l Tris pH 8.0 and ready-to-use complete protease inhibitor cocktail (Roche, Mannheim, Germany). Protein extracts were run in SDS-PAGE and analyzed on western blots incubated with primary mouse monoclonal anti-HDAC1 1:2500 (Millipore, Billerica, MA, USA; 05-100), mouse monoclonal anti-HDAC2 1:4000 (Abcam, Cambridge, MA, USA; ab12169), mouse monoclonal anti-HDAC3 1:1000 (Becton Dickinson, Franklin Lakes, CA, USA; 611124), rabbit monoclonal anti-HDAC3 1:7500 (Abcam; ab32369) and rabbit polyclonal anti-HDAC6 1:200 (Abcam; ab1440).…”
Section: Western Blotting and Immunizing Peptide Blocking Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…(20,21) The functions of RUNX2 and SOX9 are controlled by transcriptional and posttranscriptional regulation, including ubiquitination, phosphorylation, and acetylation. (12,(22)(23)(24)(25)(26)(27)(28)(29)(30) The temporal and spatial overlap of RUNX2 and SOX9 expression during embryonic development indicates a close coordination between these two key transcription factors during bone formation. (1,10,31) Indeed, it has been found that SOX9 exerts a dominant function over RUNX2 in mesenchymal precursors.…”
Section: Introductionmentioning
confidence: 99%